Implementasi Penggunaan Media Sosial Oleh Radio EBS FM Surabaya - Siahaan, Samuella Robertha Carla; Suwartiningsih, Sri; Sampoerno, Sampoerno (Innovative: Journal Of Social Science Research, 2024)
In the digital era, some radio industries are required to adapt to the development of communication technology, namely through the use of social media platforms. EBS FM is one of the youth radios in Surabaya that utilizes social media such as Instagram, TikTok and Youtube. This research aims to explain the implementation of the use of social media by EBS FM Radio Surabaya. The research method used is a qualitative approach with descriptive research type. Data was collected through interviews with 3 EBS Social Media Division Staff. The data was then analyzed using Harold Lasswell's Hypodermic Needle theory. The results showed that the use of social media conducted by EBS FM has a significant impact on radio listeners and social media users. In accordance with the assumptions of the Hypodermic Needle theory, messages delivered through social media platforms such as Instagram, TikTok and Youtube succeeded in providing direct and strong effects in the form of increased audience interaction and growth of social media followers. Another effect is that the number of incoming advertisers has also increased.